2017
DOI: 10.1007/s10620-016-4447-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Giardia in the United States

Abstract: To our knowledge, this is the largest study to date to assess predictors of giardiasis in the US. We found that male sex, being colonized with H. pylori, and residing in the Southern US are independently associated with giardiasis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Various other pathological conditions mimicking coeliac disease may cause malabsorption syndrome [ 9 ]. In Giardiasis, the villous architecture is usually normal (96% of investigated patients) [ 5 ] , mainly affecting the lamina propria, in which lymphoid hyperplasia and increased numbers of chronic inflammatory cells and eosinophils are seen. Sometimes, Giardia lamblia can induce increase of duodenal intraepithelial lymphocytes associated or not to crypt hyperplasia and different grades of villous atrophy [ 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various other pathological conditions mimicking coeliac disease may cause malabsorption syndrome [ 9 ]. In Giardiasis, the villous architecture is usually normal (96% of investigated patients) [ 5 ] , mainly affecting the lamina propria, in which lymphoid hyperplasia and increased numbers of chronic inflammatory cells and eosinophils are seen. Sometimes, Giardia lamblia can induce increase of duodenal intraepithelial lymphocytes associated or not to crypt hyperplasia and different grades of villous atrophy [ 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that about 0.11% of patients of industrialized countries presented with overt Giardia duodenalis infection [ 5 ]. However, the same countries have shown a giardia seroprevalence up to 2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is a well-known agent of one of the most extensively spread intestinal infections in temperate, tropical and subtropical zones. It has been assessed that it causes annually 280 million of diarrhoeal diseases throughout the world [58] [13,24]. In some European countries the prevalence of giardiasis in dog breeding centres reached 100 %.…”
Section: Occurrence Of G Duodenalis In Europementioning
confidence: 99%
“…The intestinal effect of the giardia parasite has probably related to several pathophysiological mechanisms. Increased apoptosis of the intestinal surface epithelium, shortening of cell cycle and disaccharides enzyme deficiency of enterocytes are few mechanisms in terms of giardial intestinal infection (Zylberberg HM et al, 2017).…”
Section: Introductionmentioning
confidence: 99%